Huanglian-Jie-Du-Tang Extract Ameliorates Depression-Like Behaviors through BDNF-TrkB-CREB Pathway in Rats with Chronic Unpredictable Stress - Ye, Yi-Lu (Evid Based Complement Alternat Med, 2017)
Neuroinflammation is considered as one of the common pathogeneses of depression. Huanglian-Jie-Du-Tang (HJDT) is a traditional Chinese herbal formula. The present study investigates the antidepressant-like effect of HJDT and its possible mechanism in rats. Rats were given HJDT (2, 4, and 8 g/kg, intragastrically), paroxetine (1.8 mg/kg, intragastrically), or an equivalent volume of saline for 42 days. The depression-related behaviors, including sucrose preference test (SPT), open field test (OFT), novel objective recognition task (NORT), and forced swimming test (FST), were detected. 5-Hydroxytryptamine (5-HT) and dopamine (DA) contents, microglial activation, proinflammatory cytokines, and brain derived neurotrophic factor (BDNF), tropomyosin receptor kinases B (TrkB), and cAMP-responsive element binding protein (CREB) expression were investigated. The results indicated HJDT (2 and 4 g/kg) dramatically ameliorated the depression-like behaviors. Also HJDT decreased the number of microglia and the proinflammatory cytokines in hippocampus. Western-blotting analysis displayed HJDT upregulated BDNF, TrkB, and pCREB/CREB expression in hippocampus. Particularly, pCREB DNA activity enhanced with HJDT treatment in hippocampus. But there was no difference in the 5-HT and DA contents with HJDT treatment. In conclusion, it was supposed that HJDT might be a potential Chinese medicine decoction for treating or alleviating complex symptoms of depression through BDNF-TrkB-CREB pathway.